2007
DOI: 10.1111/j.1742-1241.2007.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levosimendan on right ventricular systolic and diastolic functions in patients with ischaemic heart failure

Abstract: Levosimendan improves right ventricular systolic and diastolic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Levosimendan improves RV-PA coupling in experimental acute RV failure [187-189] more than dobutamine [188]. These effects have been shown clinically with improvements in RV function and reduction in PVR in ischemic RV failure [190-194], ARDS [195], and after mitral valve replacement surgery [196,197]. In chronic PH, repetitive doses reduce mPAP and PVR from baseline and improve SvO 2 [198].…”
Section: Resultsmentioning
confidence: 99%
“…Levosimendan improves RV-PA coupling in experimental acute RV failure [187-189] more than dobutamine [188]. These effects have been shown clinically with improvements in RV function and reduction in PVR in ischemic RV failure [190-194], ARDS [195], and after mitral valve replacement surgery [196,197]. In chronic PH, repetitive doses reduce mPAP and PVR from baseline and improve SvO 2 [198].…”
Section: Resultsmentioning
confidence: 99%
“…Inotropes, including epinephrine, milrinone and dobutamine, are frequently needed to augment contractility; however, milrinone and dobutamine may worsen systemic hypotension, requiring the addition of vasopressors [23,50,51]. Newer inotropes such as levosimendan have demonstrated improvements in parameters of RV function in animal models and early human studies [52,53]; however, their routine use in decompensated RV failure requires further investigation.…”
Section: Improving Right Ventricular Contractilitymentioning
confidence: 99%
“…In studies comparing levosimendan and dobutamine, some showed significant improvement in LVEF [15,20,21] both with levosimendan and dobutamine, but in a study in which patients were treated with carvedilol [17], the dobutamine group did not show an improvement in LVEF. In our study, LVEF significantly improved in the levosimendan group, but not in the dobutamine group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing levosimendan and dobutamine using echocardiographic parameters generally performed a second echocardiographic examination just after inotrope infusions [15][16][17]. We performed echocardiographic measurements 5 days after the initiation of infusions to determine whether the favorable effects of the levosimendan and dobutamine continue following infusions.…”
Section: Discussionmentioning
confidence: 99%